BRAND IMAGE DEVELOPMENT - Išoraitė, Margarita (Ecoforum Journal, 2018)
Abstract The article analyses the brand image concept, brand development stage, and the brand image importance. In order to create a strong brand image, the user must be provided with the structured information, which is stored in its memory and awareness shape and enhance the brand associations. To create a user emotional attachment to the brand, it is necessary to use the trademark emotional stimuli. The source operating user creates the brand image: the user experience (product use), friends and acquaintances assessments, information in mass communication media and brand advertising. It is important that all the listed sources to provide the same information and continually add more hints about the brand.